The DNRA-Denitrification Dichotomy Differentiates Nitrogen Transformation Pathways in Mountain Lake Benthic Habitats - Palacin-Lizarbe, Carlos; Camarero, Lluís; Hallin, Sara; Jones, Christopher M.; Cáliz, Joan; Casamayor, Emilio O.; Catalan, Jordi (Frontiers in Microbiology, 2019)
Effects of nitrogen (N) deposition on microbially-driven processes in oligotrophic freshwater ecosystems are poorly understood. We quantified guilds in the main N-transformation pathways in benthic habitats of 11 mountain lakes along a dissolved inorganic nitrogen gradient. The genes involved in denitrification (nirS, nirK, nosZ), nitrification (archaeal and bacterial amoA), dissimilatory nitrate reduction to ammonium (DNRA, nrfA) and anaerobic ammonium oxidation (anammox, hdh) were quantified, and the bacterial 16S rRNA gene was sequenced. The dominant pathways and associated bacterial communities defined four main N-transforming clusters that differed across habitat types. DNRA dominated in the sediments, except in the upper layers of more productive lakes where nirS denitrifiers prevailed with potential N2O release. Loss as N2 was more likely in lithic biofilms, as indicated by the higher hdh and nosZ abundances. Archaeal ammonia oxidisers predominated in the isoetid rhizosphere and rocky littoral sediments, suggesting nitrifying hotspots. Overall, we observed a change in potential for reactive N recycling via DNRA to N losses via denitrification as lake productivity increases in oligotrophic mountain lakes. Thus, N deposition results in a shift in genetic potential from an internal N accumulation to an atmospheric release in the respective lake systems, with increased risk for N2O emissions from productive lakes.